A comprehensive investigation of alpha decay fine structure in odd-odd and odd-even nuclei - R. Nithya Agnes; G. M. C. V. Bai; S. Selvakumar; S. C. Vella Durai (Ядерна фізика та енергетика, 2025)
We conducted a comprehensive investigation of the alpha decay fine structure in odd-even and odd-odd nuclei with atomic numbers between 95 and 101. Utilizing the cubic plus Yukawa plus exponential model, we considered the combined effects of Coulomb, centrifugal, and Yukawa plus exponential potentials as barriers for interacting fragments, supplemented by a cubic potential in the overlapping region. Our calculations of partial half-lives for alpha transitions to excited states demonstrated notable agreement with experimental data, yielding a standard deviation of 1.7671 for logarithmic half-lives. Furthermore, analysis of the fine structure revealed a linear correlation between the branching ratio and decay width in alpha decay for nuclei such as Americium, Berkelium, Einsteinium, and Mendelevium indicating a direct proportionality between these parameters.